Pengaruh Beban Kerja, Lingkungan Kerja, Pengembangan Karir dan Kompensasi Terhadap Kinerja Karyawan - Rona Tanjung; Dhenny Asmarazisa; Hafiz Aprielianto; rudi yanto batara silalahi; sahara (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
The results and analysis carried out in this study indicate that there are still problems that must be resolved. This study aims to determine the effect of workload, work environment, career development, and compensation on employee performance outcomes. This research uses quantitative research with survey method using multiple regression test. The population in this study was 63 people. Sampling was done by saturated sampling method where the total population was used as the research sample. Research data obtained by using a questionnaire instrument that has passed the validity and reliability test. The results of this study are that the workload, work environment, career development, and compensation have a joint or simultaneous effect on employee performance with the results of the F test with the acquisition of a calculated F value of 8.689 and the value of Sig. 0.000 (sign 0.000 < 0.05). Then on the results of the t test, it is known that the workload has a negative and insignificant effect on employee performance with a t value of -0.654 and sig. 0,516, the work environment variable is known to have a positive and significant effect on employee performance with a t value of 2.693 and sig. 0.009, the career development variable is known to have no positive and significant effect on employee performance with a t value of 1.410 and sig. 0.164, the compensation variable is known to have a negative and insignificant effect on employee performance with a t value of -1.049 and sig. 0.299.